Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/pathogens8030113
|View full text |Cite
|
Sign up to set email alerts
|

Serological Data Shows Low Levels of Chikungunya Exposure in Senegalese Nomadic Pastoralists

Abstract: The chikungunya virus (CHIKV) is spread by Aedes aegypti and Ae. albopictus mosquitos worldwide; infection can lead to disease including joint pain, fever, and rash, with some convalescent persons experiencing chronic symptoms. Historically, CHIKV transmission has occurred in Africa and Asia, but recent outbreaks have taken place in Europe, Indonesia, and the Americas. From September to October 2014, a survey was undertaken with nomadic pastoralists residing in the northeast departments of Senegal. Blood dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…The aim of this study was to investigate the community-based sero-prevalence of CHIKV and YFV in the South Omo Zone of Ethiopia, an endemic area for YFV.The current findings show high sero-prevalence of CHIKV infection (43.6%) in the study participants as detected by IgG capture ELISA suggesting past and/or current circulation of the virus in the study area. The proportion of the population exposed to CHIKV infection in the current study is considerably larger as compared to the IgG antibody sero-prevalence studies reported from rural coastal areas of Kenya [ 15 ], Tanzania [ 24 ], Singapore [ 25 ], Brazil [ 26 ], nomadic pastoralist of Senegal [ 27 ] and in other African countries [ 28 ]. The possible justification for such a high sero-prevalence of CHIKV infection in the present study area might be due to the presence of conducive local environmental conditions that favor vector competence in transmitting the disease [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The aim of this study was to investigate the community-based sero-prevalence of CHIKV and YFV in the South Omo Zone of Ethiopia, an endemic area for YFV.The current findings show high sero-prevalence of CHIKV infection (43.6%) in the study participants as detected by IgG capture ELISA suggesting past and/or current circulation of the virus in the study area. The proportion of the population exposed to CHIKV infection in the current study is considerably larger as compared to the IgG antibody sero-prevalence studies reported from rural coastal areas of Kenya [ 15 ], Tanzania [ 24 ], Singapore [ 25 ], Brazil [ 26 ], nomadic pastoralist of Senegal [ 27 ] and in other African countries [ 28 ]. The possible justification for such a high sero-prevalence of CHIKV infection in the present study area might be due to the presence of conducive local environmental conditions that favor vector competence in transmitting the disease [ 9 , 29 ].…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies in rural Kenya [20], Senegal [27], Tanzania [39], Bangladesh [40] and Singapore [25] reported a higher percentage of sero-prevalence of IgG antibody against many arboviruses including YFV in older individuals. Previous study in Ethiopia also showed a higher sero-prevalence of IgG antibody to YFV in individuals in the age category of 40-64 years [35].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 97%
“…The results showed that 39 nomadic pastoralist individuals were seropositive for chikungunya virus antibodies. This study suggested that there was no recent exposure to chikungunya virus in the nomadic pastoralist communities and therefore a low seroprevalence was reported in these nomadic pastoralists [142].…”
Section: Senegalmentioning
confidence: 69%
“…Finite mixture models allow characterizing the distributions of the seropositive and seronegative subgroups within bimodal datasets [ 36 ], thus being an alternative tool to estimate the probability of each sample being positive or negative to serological tests [ 37 ]. These models have been increasingly used to evaluate the performance of diagnostic tests in the absence of reference tests in humans [ 38 , 39 , 40 ] and livestock [ 41 , 42 ]. They are particularly relevant in epidemiology studies in wildlife, where reference tests or reference infected/uninfected animals are seldom available [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The multi-species nature and limited size of our dataset, including wolves and red foxes sampled post-mortem, might have affected the diagnostic performance of the serological test. However, we must emphasize the use of lung tissue extract, with the advantage of the ease of collection (simple, cheap and without the need for specialized personnel), the possibility of freezing cadavers or organs until the test is performed and the serological evaluation of animals submitted to necropsy, as being particularly useful when studying elusive wild species [ 38 , 39 , 40 ]. The representativeness of our serological study could be affected by the limited size and opportunistic nature of the sample collection.…”
Section: Discussionmentioning
confidence: 99%